Assessment of governance and ecological status of Terengganu Marine Park, Malaysia: toward marine spatial planning - Che Din Mohd Safuan; Nazli Aziz; Izarenah Md Repin; Xue, Xiong-Zhi; Abdul Rahman Muhammad Ashraf; Zainudin Bachok; Nik Nurhazirah Nik Omar; Nor Hafzan Abd Rasid; Wan Izatul Asma Wan Talaat (Penerbit Universiti Kebangsaan Malaysia, 2022)
Terengganu Marine Parks (TMP) is a 591.37 km2 marine protected area. TMP are popular tourist destinations that significantly generate revenue to the government and local businesses through tourism sector. However, the anthropogenic activities have contributed to TMP’s declining ecosystem health, particularly the coral reefs. Therefore, a sustainable ecosystem-based management is required to maintain the ecosystem. In this study, we identify issues related to the marine park’s governance, development on islands, tourist activities and coral health status in the TMP for assessing potential management strategy for conserving the ecosystem. The findings on management in TMP found that there is an overlapping in managing the marine park between the federal and state government. Unintegrated development to accommodate rising number of tourist and their activities in the marine parks are identified as the factors contributing towards degradation of the ecosystems. Relatively, reef areas close to these local pressures are in ‘poor’ condition, indicating that threats arising from the activities affecting the marine ecosystem. Hence, this study analyses the potentials in adopting Marine Spatial Planning (MSP) in the TMP for managing the conflict between user and the ecosystem. The Australian Great Barrier Reef Marine Park which applied the zoning of marine area is used as a benchmark to examine the best practices of MSP to govern the TMP. At present, we suggest using coral reef health status as an early alternative and best practice to provide different zoning criteria for strategic marine protected area (MPA) management for TMP.